Does altitude training improve sea level performance in endurance athletes? - Brash, N. (2000)
Residing at altitude allows a number of potentially beneficial physiological, ventilatory, haematological and metabolic adaptations to occur. These adaptations are postulated to improve endurance exercise performance. While is widely supported that training at altitude enhances performance at altitude, there is much less support for the view that altitude training will improve sea level endurance performance.